Awareness and Attitude of Surgeons regarding Dental Erosion on Patients Who Underwent Bariatric Surgery - Omir Aldowah (International Journal of Dentistry)
Background. The obesity epidemic is considered one of the main challenges for modern medicine. It has been proven that bariatric surgery is more effective than nonsurgical interventions to manage weight-related comorbidities. The general surgeon needs to understand how tooth erosion advances in gastroesophageal reflux in people who have had bariatric surgery. Dental erosion caused due to gastric reflux begins with the enamel, which is the tough, protective coating that covers our teeth. While it is tough, it is prone to an extremely acidic environment with a low pH, where it begins to soften and demineralize, gradually wearing away and exposing the more sensitive areas of the tooth. Because of the growing popularity of this subspecialty, general surgeons should develop a basic clinical and surgical understanding of these standard procedures and complications, regardless of their interest in obesity surgery. Aim. This cross-sectional study aimed to assess the awareness and attitude of surgeons regarding dental erosion on patients who underwent bariatric surgery. Materials and Methods. This cross-sectional study was conducted on general surgeons from different regions of Saudi Arabia who perform bariatric surgeries. Data collection was done by sending the questionnaire to the general surgeons by different means of social media (WhatsApp, e-mail, Facebook, etc.), and it was also distributed through the Saudi Arabia Society of Metabolic and Bariatric Surgery. Results. A total of 25 general surgeons responded to the survey. Half of the respondents know what dental erosion is, 52%. Most of them, 72%, are not aware of the relationship between dental erosion and acid reflux or vomiting. They reported that 52% of patients complain of gastroesophageal reflux disorder. Conclusion. The general surgeons had inadequate awareness and attitude regarding dental erosion on bariatric surgery patients. Our findings suggest that a lack of adequate awareness and a negative attitude among general surgeons are grounds for concern and that more should be done to avoid oral health complications.